Use of digital technologies in the higher education system: student attitude - Kuzmin, Sergey V. (Journal of the Belarusian State University. Sociology, 2023)
The article examines the attitude of students to digital technologies used in educational institutions, as well as the assessment of the degree of effectiveness of their application in higher education. The results of two online surveys and indepth interviews conducted with Belarusian students are analysed. Students’ high assessment of their digital competencies is recorded. Main types of student youth are identified according to the criterion of their attitude to digital innovations is proposed. The results obtained can be used to improve the efficiency of the introduction of digital technologies in the educational process, increase the quality of distance education.
Keywords: digital technologies; digital culture; educational process; digital competencies; distance learning